Western European Influences on Russian Jewelry Works in the 16th Century - Zyuzeva, Svetlana G. (Actual Problems of Theory and History of Art, 2016)
The article considers the transformation of the Renaissance decor and international Gothic art in the 16th century Russian jewelry works created in Kremlin workshops. The article focuses on the types and transformations of Renaissance ornaments encountered in the ecclesiastical artworks created with the use of various techniques such as chasing, niello and enamel on filigree. Analysis of the composition and the stylistic features of the Gospels cover, commissioned by Ivan the Terrible and created in Kremlin workshops in 1571, shows multiple analogies with Western applied art. Since the mid-16th century, masters in Kremlin workshops created a large number of works with figurative images in niello. The emergence of this technique was influenced by the development of engravings. However, the history and artistic tendencies of the time offer other precursors for the development of this type of art. Figurative images in niello were widespread in the 15th century Italian art. This technique was used by the artists from Kremlin workshops and served as an impetus for creating precious works of religious art. Transposed onto Russian works, elements of the European jewelry art underwent certain changes in accordance with customers’ taste and existing artistic tradition.
Keywords: Russian jewelry; metalwork; niello; Kremlin workshops; influence of Renaissance decoration; 16th century